Two-dimensional elastostatic continuum analysis by a boundary element technique - Iglesia, Geraldo Ramiro
An attempt is made to improve on the numerical implementation of the boundery element technique as applied to linear elastostatic analysis of plane strain and plane stress problems. The formulation and discretization of the integral equations on which the boundery element method is based are then presented. Three independent computer programs for different types of boundery elements with respect to geometry and function interpolation are developed, incorporating several salient aspects of previous works. The close agreement beyween the results obtained via these programs and the analytical solutions attests to the capabilities of the boundery element method as a useful supplement or, in some cases, a plausible alternative to existing solutions for various elastostatic problems.